Respuesta :

Use the binomial expansions of x - 1/x :

x - 1/x = 4

(x - 1/x)² = x² - 2 + 1/x² = 16

===>   x² + 1/x² = 14

(x - 1/x)³ = x³ - 3x + 3/x - 1/x³

===>   x³ - 1/x³ = 3 (x - 1/x) = 12

(x - 1/x)⁴ = x⁴ - 4x² + 6 - 4/x² + 1/x⁴

===>   x⁴ + 1/x⁴ = 4 (x² + 1/x²) - 6 = 50

Answer:

so ,

x-1/×=4

Squaring both sides

(x+1/x)² = 4²

x²+1/x²+2×x×1/x = 16

x²+1/x²+2 = 16

Again, squaring both sides

(x²+1/x²)² = 14²

x⁴+1/x⁴+2x2 = 196

x⁴+1/x⁴ = 196-2

x⁴+1x⁴=194

Step-by-step explanation:

plz mark me brainliest